1611 : authority, gender and the word in early modern England - Wilcox, Helen (Malden, MA : John Wiley & Sons Inc, 2014)
"1611: Authority, Gender, and the Word in Early Modern England explores issues of authority, gender, and language within and across the variety of literary works produced in one of most landmark years in literary and cultural history. Represents an exploration of a year in the textual life of early modern England juxtaposes the variety and range of texts that were published, performed, read, or heard in the same year, 1611 offers an account of the textual culture of the year 1611, the environment of language, and the ideas from which the authorised version of the English Bible emerged "--
Jonson's Oberon and friends: masque and music in 1611 -- Aemilia Lanyer and the "first fruits" of women's wit -- Coryats Crudities and the "travelling Wonder" of our age -- Time, tyrants and the question of authority: The Winter's Tale and related drama -- "Expresse words": Lancelot Andrewes and the sermons and devotions of 1611 -- The Roaring Girl on and off stage -- "The New World of Words": authorising translation in 1611 -- Donne's "Anatomy" and the commemoration of women: "Her death hath taught us dearely" -- Vengeance and virtue: The Tempest and the triumph of tragicomedy -- Conclusion: "This scribling age."
Includes bibliographical references and index.
Print version record and CIP data.
Keywords: 1500-1700; English literature -- Early modern, 1500-1700 -- History and criticism; Literature and society -- England -- History -- 17th century; Authority in literature; Sex role in literature; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Authority in literature; English literature -- Early modern; Literature and society; Sex role in literature; England; Electronic books; Criticism, interpretation, etc; History